(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we are interested in some results of the existence of multiple solutions for Navier boundary value problem involving degenerated (p(.), q(.))-Biharmonic and (p(.), q(.))-Laplacian operators. Our approach is based on variational method and critical point theory.